A numerical simulation method in time domain to study wind-induced excitation of traffic signal structures and its mitigation. Issue 193 (October 2019) - Jafari, Mohammad; Sarkar, Partha P.; Alipour, Alice A.
Abstract: Traffic signal structures, commonly used to control traffic, have exhibited fatigue failure in their connections due to wind-induced vibration. This study focuses on developing a generalized method to predict the coupled across- and along-wind responses of a traffic signal light structure in normal or yawed wind by combining the aerodynamic properties of such a multi-component structure with a numerical simulation technique to generate wind loads and resulting responses in the time domain. The methodology and data presented here can be applied to any signal structure to explore its dynamic behavior, estimate its fatigue life and devise mitigation means such as dampers. The tip response of the mast arm and the maximum stress at its joint were calculated for a given signal light structure and validated with field measurements to demonstrate the methodology for a range of wind speeds and yaw angles. Results indicate that yawed wind below a speed of 9 m/s from the backside of the signal light and vortex shedding of the mast arm are the primary reasons of large-amplitude vibration, and the maximum stress exceeds the endurance limit that can cause fatigue failure over time. A modified signal light design to mitigate this problem is proposed. Highlights: Fundamental wind tunnel tests to study horizontal and vertical signal lights. Extraction of aero-drag/lift and Strouhal number of signal structure's components. Proposing a practical modified signal light to prevent wind-induced vibration. Numerical simulation to predict wind-induced response/stress of signal structure. Extraction of aero-damping/stiffness by flutter derivatives of signal structure. Predicting large-amplitude response of signal structure via vortex-shedding load.